Perancangan Sistem Informasi Pengadaan Barang Pada PT. Jonan Indonesia - aryo tunjung kusumo; Saepudin, Atang (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2022)
PT. Jonan Indonesia is a company engaged in automotive manufacturing, for that we need an information system that supports employee performance, especially in the field of inventory because inventory management is an activity that is owned by every company. Problems in inventory are still done manually, especially in recording the entry and exit of goods and requests for procurement of goods. To overcome these problems, it is proposed to design this information system as a solution to the problems that exist at PT. Jonan Indonesia. The research method used is the waterfall model software development method with data collection techniques including observations, interviews and documentation studies. The tools used are using figma as a design prototype and UML (Unified Modeling Language) is used to clarify the results of the analysis and identification process. So that the design of this goods procurement information system becomes more effective.